The Association Between Case Volume and Case Processing Times in New York City. (October 2022) - Wolff, Kevin T.; Lu, Olive; Chauhan, Preeti; Leventhal, Jonathan
Past research has highlighted a number of case- and court-level characteristics that may be associated with differences in case processing time, yet other factors remain relatively unexplored. Drawing on an extensive case-level data set of misdemeanor and felony cases resolved in New York City's court system, the current study contributes to our knowledge of case processing time by examining the association between the relative volume of arraignments (at the borough level) and case processing time. The analysis employs standard regression techniques to assess the relationship between case volume and case processing time while controlling for a number of individual- and case-level characteristics. Results suggest the relative volume of cases coming into the court system is positively associated with case processing time, net of several relevant case-level characteristics. These findings contribute to the small and inconsistent findings reported in prior work. Implications of these findings for future research and criminal justice policy are discussed.